Urgensi Amandemen dalam Konstitusi Undang-Undang Perbankan di Indonesia - Ahmad Muhtar Syarofi (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2017)
In today's modern economy era, the role of banking institutions is very important. In Indonesia the role of banking institutions is so increasing that it reaches about 99% of the national financial system. Given such an important role of the institution, it should be supported by a strong and strong, credible (reliable) legal and regulatory tool. Strong, strong and credible in the sense of their contents-the articles are not contradictory to each other, are not often revised / amended, neither misinterpreted and applicable. The Law Regulating Banking Law No. 7 of 1992 was amended by Act No. 10 of 1998 on Banking, Act No.23 of 1999 which amended by Act No. 3 of 2004 and Act No. 6 of 2009 on Bank Indonesia, Law Number 21 of 2008 concerning Sharia Banking (July 16, 2008); Law No. 21 of 2011 on the Financial Services Authority. This paper draws the conclusion that it is necessary to amend the law regulating of OJK, considering that OJK as the sole overseeing agency and investigator of economic activity in Indonesia, needs other institution to guard the developmnet of national banking in order to be health, grow fairly and support national economic development continuous. Keyword: Amendment, Law, Banking